FAWAG using CO2 philic surfactants for CO2 mobility control for enhanced oil recovery applications - Sagir, M. (Society of Petroleum Engineers, 2014)
The application of CO2 injection for mobilization of trapped oil in porous media is the most frequently applied method for EOR projects. Despite of the fact that the CO2 injection can effectively mobilize the trapped oil, many problems such as viscous fingering, gravity override, high ratio of CO2 to oil produced and early breakthrough are required to be resolved. In this context, the injection of surfactant solution for the reduction of CO2 mobility is a promising method. However, until now surfactants usage for mobility control is facing many challenges such as, adsorption of surfactants on rock, requirement of copious amounts of water, and loss in the thief zones of reservoir. These challenges can effectively be reduced by employing CO2 soluble surfactants, which have exhibited more practical advantages over conventional surfactants. A study has been conducted to evaluate new CO2 soluble surfactants for the CO2 mobility control for EOR applications. The IFT between CO2 and synthesized surfactants solution was studied for the initial screening process and is reported. The coreflood experiments were conducted by using Berea core sample in order to measure the mobility reduction factor (MRF). The MRF value of 3.1 was obtained by the incorporation of 0.5 of novel CO2 philic foaming agent. Moreover, it was observed that the IFT between CO2 and brine appreciably decreased by using the surfactant in 0.5 concentration. Coreflood results showed that, as compared to conventional surfactants, newly developed CO2 philic surfactants significantly reduced the mobility of the injected CO2. Â© Copyright 2014, Society of Petroleum Engineers.